Support of subjects of small and average business in the CIS countries (Uzbekistan, Azerbaijan, Kazakhstan, Belarus) - E. A. Zolotova (Путеводитель предпринимателя)
The analysis of support of subjects of small and average business in the CIS countries is presented in article, Uzbekistan, Azerbaijan, Kazakhstan, Belarus are regarded; their results, new maintaining and regulations.